Museum in Context - Wilkens, Katharina (Journal of religion in Europe, 2011)
In using the critical term museality in aesthetics of religion, it is our aim in this article to reveal the socio-cultural embeddedness of museums in Western societies and beyond. To do this we draw on two distinct cultural and sociological models of society, dispositive theory and Luhmann's communicational systems theory. Dispositive theory allows us to include non-discursive practices and materialisations in the aesthetic analysis of religious identification strategies mediated through museums and exhibitions. The boundaries, environment and self-referentiality of the system museum are discussed with a view to the shifting place and visibility of religious and secular messages in museum contexts. The focus on museality leads beyond museums to discover object wanderings, religious re-interpretations and museum displays in a number of other socio-cultural fields.